RESEARCH OF ETHNIC ASPECTS OF INFORMATION PERCEPTION IN CURRENT MASS MEDIA - Taras S. Kuzin (Статистика и экономика)
Some results of a theoretical and empirical research carried out with the purpose of revealing and assessment of ethnopsychological features of perception of mass media messages are reflect in the article. The direct presentation of this problem with taking into account the national mentality of students and cadets in the domestic and foreign science was not considered, as well as methods to identify them weren’t developed. The received theoretical and empirical results are a scientific basis for introduction of technologies of development of professionally important qualities of specialists into practice.